Complement factor H protects mice from ischemic acute kidney injury but is not critical for controlling complement activation by glomerular IgM - Goetz, Lindsey (Eur J Immunol, 2018)
Natural IgM binds to glomerular epitopes in several progressive kidney diseases. Previous work has shown that IgM also binds within the glomerulus after ischemia/reperfusion (I/R) but does not fully activate the complement system. Factor H is a circulating complement regulatory protein, and congenital or acquired deficiency of factor H is a strong risk factor for several types of kidney disease. We hypothesized that factor H controls complement activation by IgM in the kidney after I/R, and that heterozygous factor H deficiency would permit IgM-mediated complement activation and injury at this location. We found that mice with targeted heterozygous deletion of the gene for factor H developed more severe kidney injury after I/R than wild-type controls, as expected, but that complement activation within the glomeruli remained well controlled. Furthermore, mice that are unable to generate soluble IgM were not protected from renal I/R, even in the setting of heterozygous factor H deficiency. These results demonstrate that factor H is important for limiting injury in the kidney after I/R, but it is not critical for controlling complement activation by immunoglobulin within the glomerulus in this setting. IgM binds to glomerular epitopes after I/R, but it is not a significant source of injury.